Hubungan antara Religiusitas dan Konformitas Teman Sebaya dengan Perilaku Mengonsumsi Minuman Alkohol pada Mahasiswa - Dinda Laila Arfianie; Latifah Nur Ahyani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to empirically examine the relationship between religiosity and peer conformity with alcohol consumption behavior among college students. The research method utilized a quantitative approach by distributing psychological scales online to 77 student respondents. The instruments used were the Alcohol Consumption Behavior Scale, Peer Conformity Scale, and Religiosity Scale, which were analyzed using multiple linear regression via SPSS. The results showed a highly significant simultaneous relationship between religiosity and peer conformity with alcohol consumption behavior among college students ($R = 0.731$; $p < 0.01$), contributing an effective variance of 53.4%. Partially, religiosity had a highly significant negative relationship with alcohol consumption behavior ($r = -0.725$; $p < 0.01$), meaning that higher religiosity predicts lower alcohol consumption. Meanwhile, peer conformity also demonstrated a significant negative relationship ($r = -0.349$; $p < 0.05$), indicating that conformity can reduce alcohol consumption when individuals are within a peer group that possesses positive social norms. In conclusion, alcohol consumption behavior among college students is driven by the integration of internal factors in the form of self-control from religiosity and external factors from adaptation to peer group norms.